Fluorescein Retinal Angiography in Newly Diagnosed Type 2 Diabetic Patients at the Yaoundé Central Hospital: Fluorescein retinal angiography in newly diagnosed type 2 diabetic patients - Dohvoma Viola Andin; Ebana Mvogo SR; Dehayem M; Nouebissi FL; Mvilongo TC; Akono Zoua ME; Nguena MB; Epee E; Sobngwi E; Ebana Mvogo C (HEALTH RESEARCH IN AFRICA, 2023)
ABSTRACT Aim. To describe retinal complications of diabetes on retinal angiograms in newly diagnosed type 2 diabetic patients at the Yaoundé Central Hospital. Methods. A cross-sectional descriptive study was carried out between January 8th and May 31st 2018. Consenting newly diagnosed type 2 diabetic patients were recruited from the 2 diabetic clinics and the ophthalmology unit of the Yaoundé Central Hospital. Retinal angiography was done after history-taking, visual acuity measurement and slit lamp examination. Results. We included 82 patients (45 males and 37 females). Ages spanned 31 and 82 years, with a mean of 53.6 ± 11.5. Hypertension was present in 30.5% of patients (n=25). Glycated haemoglobin was available for 44 patients (53.66%), amongst whom, 72.7% had values >8%. The prevalence of diabetic retinopathy was 9.8% (n=8) and all were non-proliferative. Diabetic maculopathy was present in 50% of those with diabetic retinopathy. Conclusion. Despite the low prevalence of diabetic retinopathy amongst newly diagnosed diabetic patients, half of the patients with diabetic retinopathy present with diabetic maculopathy, which could compromise visual outcome. Ophthalmic examination is necessary at the time of diagnosis of type 2 diabetes as a baseline for future screenings and to manage retinal complications which may already be present. RÉSUMÉ But. Décrire les complications rétiniennes du diabète à partir des angiographies des patients diabétiques de type 2 nouvellement diagnostiqués à l’Hôpital Central de Yaoundé. Méthodes. Nous avons mené une étude transversale et descriptive du 08 janvier au 31 mai 2018. Les patients diabétiques de type 2 nouvellement diagnostiqués ayant donné leur consentement ont été recrutés dans les 2 centres de prise en charge de diabète et dans le service d’ophtalmologie de l’Hôpital Central de Yaoundé. L’angiographie à la fluorescéine était réalisée après l’interrogatoire, la mesure de l’acuité visuelle et l’examen du segment antérieur à la lampe à fente. Résultats. Nous avons colligé 82 patients (45 de sexe masculin et 37 de sexe féminin). La moyenne d’âge était 53,6 ± 11,5 (extrêmes : 31 et 82 ans). L’hypertension artérielle était présente chez 30,5% des patients (n=25). Le taux d’hémoglobine glyquée avait été réalisé chez 44 patients (53,66%), parmi lesquels 72,7% avaient une valeur >8%. La prévalence de la rétinopathie diabétique était de 9,8% (n=8) et tous les cas étaient au stade non proliférant. La maculopathie diabétique était présente chez 50% de ceux-ci. Conclusion. Malgré la faible prévalence de la rétinopathie diabétique au moment du diagnostic du diabète, la moitié des patients avec la rétinopathie ont une maculopathie qui peut compromettre le pronostic visuel. L’examen ophtalmologique dès la découverte du diabète de type 2 est indispensable comme référentiel pour le suivi et pour dépister et traiter les complications qui peuvent déjà être présentes.